Varicocele in Brothers of Patients With Varicocele - Beigi, Faramarz Mohammadali; Mehrabi, Sadrollah; Javaherforooshzadeh, Ahmad (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar {mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: The aim of this study was to evaluate varicocele patients’ brothers to determine whether they are at a higher risk of varicocele than the general population of men. Materials and Methods: A total of 56 patients with varicocele and their 131 brothers (> 16 years old) were evaluated. The brothers had no complaints of infertility, pain, or cosmetic problems. They were all examined for varicocele. One hundred and fifty men who referred for employment medical examinations were considered as the control group. Results: Of the subjects, 39 (69.6%) had grade III varicocele. Sixty (45.8%) of the brothers had varicocele. The grade of varicocele was III in 16 (26.7%) brothers. In the control group, varicocele was present in 15 (10%) which was grade III in 5 (33.3%). The frequency of varicocele was 4.5-fold greater in the brothers of the patients than the controls (P < .001). Also, the frequency of grade III varicocele was significantly more than grades I and II in the patients in comparison with their brothers and controls with varicocele (P < .001). There was no significant difference in the grades between the controls and the patients’ brothers (P = .31). The frequency of bilateral varicocele was not statistically different between the three groups (P = .14). Conclusion: Our findings showed that a significant increase is seen in the prevalence of varicocele in the patients’ brothers compared to men in the general population, warranting evaluation of the first-degree relatives of men who present with varicocele.